OPINIONS DES JEUNES MAROCAINS RELATIVES AU TABAGISME - Sabah, Selmaoui; Boujemaa, Agorram; Anouar, Alami; Salah-eddine, Khzami (European Scientific Journal, ESJ, 2015)
Smoking is a major public health problem. Indeed, the tobacco’s impact on health and the environment is well established both in active smokers than among passive smokers. Morocco is considered as one of the biggest tobacco users in the Mediterranean and young children are the main victims of the tobacco trade. The smoking prevalence rate in Morocco is high among young people. Faced with this situation and therapeutic difficulties, prevention remains the best way to educate young people. We ask the following questions: - What are the causes that lead young people to give to smoking? - Do they know that passive smoking? - Are they aware of the anti smoking law? - In their opinion, what is the most efficient way to fight against this scourge? The tool of investigation and collection of information used is a questionnaire to young people (pupils and students) smokers and nonsmokers whose age varies between 13 and 25 years. The questionnaire was validated and tested well before administration. The results we collect might as well argue that young smokers are given to tobacco under the influence of a peer who push them to try cigarettes or other drugs. Family problems and social pressure were also the source of their smoking behavior and that contributed to the aggravation of tobacco use and the resurgence of the scourge. Similarly non smokers youth think also the same causes of smokers addictive behavior. These young people questioned whether smokers or non-smokers seem to ignore what is passive smoking. They are not aware of the anti-tobacco law that bans smoking in public places as well as its sales to minors and the legal provisions on sanctions. The respondents believe that the most effective way to reduce smoking especially among young people is education. Preventive education addictive behavior in the family, at school and on the streets to develop life skills for young people to make informed and responsible choices for themselves as screw towards others and the environment.